EL DEBATE LITERARIO EN EL S. III A.C. - Guillén Selfa, Luis (Myrtia, 1996)
The aim of this paper is to place the 3rd century B.C. literary debate in due perspective. Both aesthetic and purely literary considerations are taken into account, together with the contemporary cultural and philosophical background. The controversy is thus presented as a complex movement rather than as a debate.